Students' Coping Mechanism in Reducing Their Speaking Anxiety - Fatimah Zahra; Dyah Ciptaningrum (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2025)
With the increasing demand for English as an international language, speaking skills should be further developed. However, many students still experience anxiety when speaking English. This study aimed to determine students' levels of English-speaking anxiety. This research aimed is to identify their coping mechanisms. This research used a mixed-method approach with two stages. The quantitative instrument was the FLCAS questionnaire, while the qualitative instrument was an interview guide. The participants were 35 high school students in Bantul. The FLCAS results showed that 14 students have mild anxiety, 13 have moderate anxiety, 4 are relatively relaxed, 3 experience high anxiety, and 1 has no anxiety. Two students from each anxiety level (mild, moderate, and high) were selected using purposive sampling to explore their coping mechanisms. The interviews indicated that most students used emotion-focused coping, while some also applied problem-focused strategies. The results of this research enable future research to further examine the long-term effectiveness of different coping strategies in reducing speaking anxiety.